Evaluation of School Health Services in Nomadic Primary Schools in Southwestern Nigeria - Ibhafidon, A. A.; Ejifugha, A.U. (Richtmann Publishing, 2012)
Schools health services are procedures which are established to appraise the health status of pupils andschool personnel, counsel pupils, parents and others concerning appraisal findings, carry out follow-upservices, provide emergency care of injuries and sudden illness, help prevent and control communicablediseases and encourage the correction of remedial defects. Previous studies have shown low levels ofpositive health attitude and practices, resulting in a high prevalence of malaria, tooth decay.Gastrointestinal and skin diseases. Therefore, this study evaluated school health services in nomadicprimary schools in Southwestern Nigeria in order to identify areas needing improvement. The studyemployed descriptive survey research design. Total enumeration procedure was used to include all the1,005 nomadic primary school teachers in Southwestern Nigeria. The instrument used for the study wereobservation checklist, Focus Group Discussion Guide, and questionnaire which was validated through theuse of test-retest method with a reliability coefficient of 2.88. Five hypotheses were postulated and tested at0.05 alpha level using Binomial test. Based on the result four hypotheses were accepted while one was notaccepted as shown by the observed binomial proportion of respondents’ responses to the statements on allthe variable. The results showed that the following activities were not significantly carried out in Nomadicprimary schools in Southwestern Nigeria: health appraisal (0.2895;<0.05); follow-up services (0.407;P<0.05); emergency care and first aid (0.3602; P<0.05). However, communicable diseases weresignificantly controlled in the school (0.6218; p<0.05). It was concluded that school health services was notgiven necessary attention in nomadic primary schools in Southwestern Nigeria. Hence, it wasrecommended that for a functional school health services, the stakeholders (Federal, State, LocalGovernments and the nomadic communities) should endeavour to put in place health appraisal, healthguidance and counseling follow-up services and emergency care and first aid in nomadic primary schoolsin Southwestern Nigeria.